“Ruin Poetics” in Chateaubriand’s Works of the1800s – 1820s (Proceedings of Southern Federal University. Philology, 2018)
Andrey Yu. Chernukhin (Rostov-on-Don, Russian Federation)The article studies the comprehension and artistic realization of ruin theme in Chateaubriand’s creative works over the period of 1800s– 1820s. In terms of “ruin poetics” “The Genius of Christianity”, short novels “Atala” and “René” as well as “Voyage en Italie” and a short story “The Adventures of the Last Abencerrage” are analyzed. The aesthetic, religious, psychological and artistic aspects are considered. The links with the Enlightenment epoch and Diderot’s aesthetical views are observed.Key words: Chateaubriand, “ruin poetics”, romanticism, psychologism, romantic historicism, Diderot.DOI 10.23683/1995-0640-2018-1-38-46